Disentangling Aging and Mood Effects on Emotional Memory - Tamera, Kylee; Kannampuzha, Courtney; Ta, Viviane; Hot, Pascal; Davidson, Patrick S. R. (Frontiers in Behavioral Neuroscience, 2022)
Older adults tend to be in a more positive mood than young adults, and tend to remember positive information more often than negative information, but the link between their positive mood and their positive memory bias has not often been explored. In this study, we manipulated young and older adults’ moods prior to their completing an emotional memory task. For mood manipulation, young (n = 147) and older (n = 111) adults viewed a positive, negative, or neutral video lasting 3 minutes. To validate the mood induction, we collected self-reported ratings of valence and arousal (affective slider; Betella & Verschure, 2016) at baseline, after the video, and after the memory task. The memory task consisted of incidental encoding of 30 intermixed pictures (10 positive, 10 negative, 10 neutral valence), followed by free recall. The mood manipulation changed people’s self-reported valence, yet it did not influence self-reported arousal. The memory task revealed a consistent negativity bias in young adults. Older adults recalled negative and positive pictures equally well in all conditions. After viewing a negative video, they recalled positive pictures more often than neutral pictures, but did not show the same advantage for negative pictures over neutral pictures. This positive memory advantage was weaker in the positive mood condition. Therefore, mood manipulation influenced in part older adults’ emotional memory bias, showing some signs of mood incongruence which we discuss in terms of emotion regulation. This shows the importance of accounting for mood differences in studies on aging and memory. The robust age group differences support the view that the positivity effect in aging is the result of a negativity bias that fades with age.